Board Gender Diversity and Corporate Tax Avoidance: Examining the Moderating Effect of CSR - Latifahiansyah, Inas; Soerono, Ayu Noorida; Ismawati, Iis (PT. EQUATOR SINAR AKADEMIA, 2025)
This study examines the effect of female board directors on corporate tax avoidance, with Corporate Social Responsibility (CSR) as a moderating variable. The study uses a quantitative method with secondary data from the annual reports of 30 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, yielding 150 observations. The data are analyzed using multiple regression and moderated regression analysis (MRA). The results indicate that board gender diversity has a significant negative effect on corporate tax avoidance, suggesting that female directors restrain tax avoidance practices. However, CSR does not moderate this relationship. This research provides originality by integrating transformational leadership theory with agency theory to explain the direct role of female directors in a developing country context. The findings imply that policymakers and corporations can benefit from promoting gender diversity on boards as a mechanism to enhance tax compliance, while also recognizing that CSR disclosure alone may not be sufficient to influence the ethical decision-making dynamics related to taxation.